Compartmental Surgery With Microvascular Free Flap Reconstruction in Patients With T1–T4 Squamous Cell Carcinoma of the Tongue: Analysis of Risk Factors, and Prognostic Value of the 8th Edition AJCC TNM Staging System - Carta, Filippo; Quartu, Daniela; Mariani, Cinzia; Tatti, Melania; Marrosu, Valeria; Gioia, Edoardo; Gerosa, Clara; Zanda, Jacopo S. A.; Chuchueva, Natalia; Figus, Andrea; Puxeddu, Roberto (Frontiers in Oncology, 2020)
Compartmental surgery and primary reconstruction with microvascular free flaps represent the gold-standard in the treatment of oral tongue squamous cell carcinoma (OTSCC). However, there are still unclear clinical features that negatively affect the outcomes. This retrospective study included 80 consecutive patients with OTSCC who underwent compartmental surgery and primary reconstruction by free flap. The oncologic outcomes, the reliability of the 8th edition American Joint Committee on Cancer (AJCC) staging system and the prognostic factors were evaluated. Fifty-nine males and 21 females (mean age 57.8 years, range 27-81 years) were treated between November 2010 and March 2018 (one patient had two metachronous primaries). Seventy-one patients (88.75%, 52 males, 19 females, mean age of 57.9 years, range of 27-81 years) had no clinical history of previous hand and neck radiotherapy and were considered as naïve. Histology showed radical surgery on 80/81 lesions (98.8%), with excision margins greater than 0.5 cm, while in 1 case (1.2%), a close posterior margin was found. According to the 8th AJCC classification, 37 patients (45.7%) were upstageded shifting from the clinical to the pathological stage, and 39 (48.1%) showed an upstaging while shifting from the 7th to the 8th AJCC staging system (no tumors were downstaged). Nodal involvement was confirmed in 33 patients (40.7%). Perineural and lymphovascular invasion were present in 9 (11.1%) and 11 (13.6%) cases respectively. Twenty-two patients (27.1%) underwent adjuvant therapy. The five-year disease-specific, overall, overall relapse-free, locoregional relapse-free and distant metastasis-free survival rates were 73.2%, 66.8%, 62.6%, 67.4% and 86%, respectively. Patients with a lymph node ratio > 0.09 experienced significantly worse outcomes. Univariate analysis showed that patients with previous radiotherapy, stage IV disease, nodal involvement, and lymphovascular invasion had significantly worse outcomes. Multivariate analysis focused naive patients showed that lymphovascular invasion, advanced stage of disease, and node involvement resulted as reliable prognostic factors, and patients with the same tumor stage and histological risk factors who did not undergo adjuvant therapy experienced significantly worse outcomes. In our series, surgery played a major role in the treatment of local extension; adjuvant therapy resulted strictly indicated in patients with advanced-stage disease associated with risk factors.